2019
DOI: 10.1371/journal.pone.0226730
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with atrial fibrillation: The role of symptoms, comorbidities, and the type of atrial fibrillation

Abstract: AimsThis study aimed to analyse health related quality of life (HRQoL) for patients with different atrial fibrillation (AF) types and to identify patient characteristics, symptoms and comorbidities that influence HRQoL.MethodsWe used baseline data from the Swiss Atrial Fibrillation (Swiss-AF) study, a prospective multicentre observational cohort study conducted in 13 clinical centres in Switzerland. Between April 2014 and August 2017, 2415 AF patients were recruited. Patients were included in this analysis if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 33 publications
2
29
0
3
Order By: Relevance
“…26 In the study by Wojaszel et al, AF was related to significantly higher scores of FS, independently from age, gender, multimorbidity, and polypharmacy. 31 In our study, the regression analysis identified FS as a statistically significant independent predictor of increased arrhythmia symptom severity in ASTA II and decreased QoL in ASTA III. The issue of QoL is now often addressed in medicine.…”
Section: Discussionsupporting
confidence: 51%
“…26 In the study by Wojaszel et al, AF was related to significantly higher scores of FS, independently from age, gender, multimorbidity, and polypharmacy. 31 In our study, the regression analysis identified FS as a statistically significant independent predictor of increased arrhythmia symptom severity in ASTA II and decreased QoL in ASTA III. The issue of QoL is now often addressed in medicine.…”
Section: Discussionsupporting
confidence: 51%
“… 7 The EHRA score is considered one of the strongest predictors of QoL, regardless of the type of AF, and is commonly used to assess improvement in symptoms after treatment of AF. 8 …”
Section: Introductionmentioning
confidence: 99%
“…The majority of published studies on QoL in AF relate to the response to rhythm control therapies such as antiarrhythmic drugs or ablation. In contrast, patients with permanent AF have even worse QoL [6], account for around 50% of all patients, and yet we lack an adequate description of underlying factors [7].…”
Section: Introductionmentioning
confidence: 99%